Perception of different stakeholders and Practice of Disabilityinclusive education at secondary schools in Bangladesh (Teacher’s World: Journal of Education and Research, 2023)
The paper is focused on the status of disability-inclusive education from policies to practices at the secondary level of education in Bangladesh. The paper explored the classroom teaching[1]learning practice and available resources in secondary schools in this regard. It also attempted to explore the perception of different stakeholders towards disability-inclusive education. 10 secondary schools were selected from Dhaka and Rajshahi divisions following a convenient sampling technique. Data were gathered from teachers, students, and parents of that level and disability-inclusive education experts using the Interview and FGD method. Data were processed and analyzed using Barun and Clarke’s (2006) six-step thematic analysis technique. The results have shown that participation of students with disabilities in secondary schools is nominal and the dropout rate is higher. Though teachers and parents expressed a sympathetic view toward disability, special schooling is the better option for students with a disability according to their opinion. Thus, they lack a positive attitude toward disability inclusion. Moreover, school infrastructure and teaching-learning are not very convenient. Therefore, the study recommends that training facilities, available resources, and the existing infrastructure be redesigned and enhanced; curriculum modification and adaptation in the assessment system should be introduced to successfully implement disability-inclusive education.Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.167-184